Clinical outcome in 23 dogs with exocrine pancreatic carcinoma. (28th August 2020) - Pinard, Christopher J.; Hocker, Samuel E.; Weishaar, Kristen M.
Abstract: Exocrine pancreatic carcinoma is uncommon in the dog and the veterinary literature surrounding the disease is minimal. Twenty‐three cases of canine exocrine pancreatic carcinoma were reviewed in a retrospective manner to obtain information on clinical presentation, behaviour and survival associated with the disease. Presenting clinical signs were nonspecific and included anorexia, lethargy, vomiting and abdominal pain. The overall median survival time was only 1 day but was confounded by the large number of dogs that were euthanized shortly after diagnosis. Metastatic disease was detected in 78% of cases at the time of diagnosis, attesting to the aggressive nature of the disease. Neither lymph node metastasis, tumour size nor tumour location had an impact on overall survival. Only one patient was a previous diabetic who is contrary to reports of the disease in people and felines. This retrospective study reaffirms the need for early detection measures to optimize disease control. However, the benefits of therapy with surgery or radiation and adjuvant chemotherapy remain to be elucidated in dogs with exocrine pancreatic carcinoma.